ENHANCING CYCLIC STABILITY OF LITHIUM-ION BATTERIES THROUGH THE DEVELOPMENT OF ONE-DIMENSIONAL NICKEL-RICH NCM CATHODE MATERIALS - Toktamyssova, Alina (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Free-standing one dimensional (1D) LiNi0.8Co0.1Mn0.1O2 (Lithium nickel cobalt manganese oxides, NCM811) cathode material was synthesized by electrospinning method for lithium-ion batteries (LIBs) and the conditions of the sintering process for obtaining successful structure of the material were optimized. The morphology, physico-chemical properties, and structure of the resulting 1D NCM811 samples were studied using scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction analysis (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), and thermogravimetric analysis (TGA). XRD patterns of the studied material showed a series of peaks that entirely corresponded to the diffraction patterns of NCM811, while indicating low cation mixing degree I(003)/I(104) = 1.64. Cyclic voltammetry (CV) and galvanostatic charge-discharge cycling (GDC) were used to examine the electrochemical characterizations of 1D NCM811. Obtained electrochemical properties of the 1D NCM811 demonstrated that compared to conventional slurry casted electrodes (electrode-specific capacity-49 mAh g⁻¹), the free-standing electrodes with low cation mixing degree have stable electrode-specific capacity about 150-160 mAh g⁻¹ within the initial 20 cycles. Therefore, it is highly expected that the results may present some novel concepts in the development of free-standing 1D NCM811 cathodes and morphology modification, which will be helpful in the rational design and production of high energy density LIBs.
Keywords: Li-ion batteries; NCM cathode; Electrospinning; type of access: embargo